2022
DOI: 10.3389/fgene.2022.1070971
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and genetics of hepatoblastoma: Linkage and treatment

Abstract: Hepatoblastoma is a malignant embryonal tumor with multiple differentiation modes and is the clearest liver malignancy in children. However, little is known about genetic and epigenetic events in Hepatoblastoma. Increased research has recently demonstrated, unique genetic and epigenetic events in Hepatoblastoma, providing insights into its origin and precise treatment. Some genetic disorders and congenital factors are associated with the risk of Hepatoblastoma development, such as the Beckwith-Wiedemann syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 129 publications
0
0
0
Order By: Relevance
“…In agreement with these reports, recent studies revealed that the inhibition of methyltransferase activity of G9a/DNMT1 reduces the proliferation of HBL cells and growth of HBL spheroids [17]. The critical role of microRNAs, as well as the role of LncRNAs in the development of HBL, was also recently described in several papers [14,18,19]. An additional epigenetic pathway in hepatoblastoma and in HCC is related to the modification of m6A in mRNAs [20,21].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…In agreement with these reports, recent studies revealed that the inhibition of methyltransferase activity of G9a/DNMT1 reduces the proliferation of HBL cells and growth of HBL spheroids [17]. The critical role of microRNAs, as well as the role of LncRNAs in the development of HBL, was also recently described in several papers [14,18,19]. An additional epigenetic pathway in hepatoblastoma and in HCC is related to the modification of m6A in mRNAs [20,21].…”
Section: Introductionsupporting
confidence: 61%
“…Recent studies of HBL have identified epigenetic changes in the levels of DNA methylation, microRNAs, LncRNAs and histone modification [14]. Rivas and colleagues first found that DNA methylation is an essential epigenetic player in HBL [15].…”
Section: Introductionmentioning
confidence: 99%